Thank you for the opportunity to help you with your question!

-------------------------------------------------------------------------

x + 3y = 9 ---(1)

3x - y = 7 ---(2)

Multiply equation (1) by 3

3x + 9y = 27 ---(3)

Subtract equation (2) from equation (3)

3x + 9y - (3x - y) = 27 - 7

3x + 9y -3x + y = 20

10y = 20

y = 20/10

y = 2

Substitute value of y in equation (1)

x + 3(2) = 9

x + 6 = 9

x = 9 - 6

x = 3

So the system of equations has one and only one solution and

the solution is (3, 2).

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up